Physiological and molecular implications of plant polyamine metabolism during biotic interactions - Jiménez Bremont, Juan F.; Marina, María; Guerrero-González, Maria de la Luz; Rossi, Franco R.; Sánchez-Rangel, Diana; Rodríguez-Kessler, Margarita; Ruiz, Oscar A.; Gárriz, Andrés (Frontiers in Plant Science, 2014)
During ontogeny, plants interact with a wide variety of microorganisms. The association with mutualistic microbes results in benefits for the plant. By contrast, pathogens may cause a remarkable impairment of plant growth and development. Both types of plant-microbe interactions provoke notable changes in the polyamine (PA) metabolism of the host and/or the microbe, being each interaction a complex and dynamic process. It has been well documented that the levels of free and conjugated PAs undergo profound changes in plant tissues during the interaction with microorganisms. In general, this is correlated with a precise and coordinated regulation of PA biosynthetic and catabolic enzymes. Interestingly, some evidence suggests that the relative importance of these metabolic pathways may depend on the nature of the microorganism, a concept that stems from the fact that these amines mediate the activation of plant defense mechanisms. This effect is mediated mostly through PA oxidation, even though part of the response is activated by non-oxidized PAs. In the last years, a great deal of effort has been devoted to profile plant gene expression following microorganism recognition. In addition, the phenotypes of transgenic and mutant plants in PA metabolism genes have been assessed. In this review, we integrated the current knowledge on this field and analyze the possible roles of these amines during the interaction of plants with microbes.